Determination of Albumin Level of Patin Fish from Kahayan River, Central Kalimantan by Biuret Method - Yuliana, Yuliana; Pramudita, Dimas; Simbolon, Wenika; Imelya, Marsya (ALKIMIA, 2023)
Albumin plays important roles in the health of the body, such as stabilizing intravascular fluid pressure, facilitating molecular transport, and facilitating fluid movement in the body. The high cost of albumin, the limited availability of albumin sources, and the uncertainty surrounding its halal status underscore the imperative for this research. The objective of this study was to identify alternative sources of albumin, with a focus on exploring non-fish sources. Patin fish, a species endemic to Central Kalimantan, is a promising alternative due to its abundance and cost-effectiveness. The albumin content of steamed and dipped patin fish at 10, 15, 20, and 25 minutes was determined using the biuret method. The findings indicated that steaming yielded higher albumin content than dipping, with values of 4.41% and 3.88%, respectively. The optimal steaming duration was determined to be 15 minutes, while the optimal dipping duration was 20 minutes. These findings suggest that steaming may serve as a viable alternative source of fish albumin, offering a more economical option than snakehead fish.